PKM TELEFARMASI DALAM KEPATUHAN TERAPI HIPERTENSI DAN PERSPEKTIF MASYARAKAT - Krisanti, Elsa Annisa; Suryani, Suryani (LPPM Universitas Bina Bangsa, 2024)
Hypertension is the most common chronic disease characterized by a constant increase in arterial pressure of more than 130/80 mmHg. Hypertension is a disease that contributes to the development of stroke, myocardial infarction, heart failure and kidney failure, so it is necessary to control hypertension throughout life by maintaining patient compliance so that there is no spike in blood pressure which causes damage to body organs. In the era of industrial revolution 5.0 with unlimited digital Internet, the ease of remote interaction without time constraints provides the opportunity to check the compliance of hypertensive outpatients wherever they are. The method used is a narrative review. Results of journal articles published through online media from 2016 to 2023. Manual search for articles from Pubmed, Science Direct, Google Scholar, JMIR Publications, and SagePub databases. The research results show that telepharmacy has an impact on controlling blood pressure in hypertensive patients